Impact of improper land use changes on flash flood and river system: a case of Sg Pusu - Al-Mamun, Abdullah; Salleh, Md. Noor; Nuruzzaman, Md.; Mohd. Dom, Norlida; M. Amin, Mohd. Zaki; Abu Eusuf, Muhammad; Khan Chowdhury, Ahmed Jalal (Asian Research Publishing Network (ARPN), 2016)
The impact of land uses can cause significant changes in the hydrological regime of a river basin. Sg. Pusu is a recent example in Malaysia, which is going through indiscriminate changes in the landuses. This study was conducted in response to the recent severe flash flood occurred on 4th June, 2014 due to high rainfall intensity of 82.4 mm/hr which lasted about 2 hours. The flooding depth varied from 0.3 to 1.0 m and the flash flood duration was about 1.5 hours. Although the duration was short but it damaged 12 cars, inundated 2 blocks of the hostels (Mahallah) and caused inconvenience to the staff and students of the campus. The drainage and river systems of the campus was functioning properly as the seven ponds and lakes constructed along the rivers and tributaries could reduce the peak flows coming from the upstream areas. However, due to improper land clearing from 2009 and onwards, the peak flows during the rain events have increased significantly, the lakes and ponds constructed by IIUM has silted up and lost their flow reduction ability. As a result the flash flood incidents have increased compared to the past records. The development activities in the upstream areas not only have increased the severity of flood in the campus but also caused sediment related water pollution turning the Sg. Pusu and its tributaries muddy all the time. Due to the improper land clearing activities in the upstream areas, the runoff peak flow and sediment load has increased tremendously, which the existing lakes, ponds, rivers, culverts and drainage system are unable to cope with. The river is also badly affected by the improper land clearing activities at the upstream areas. The Turbidity and TSS values at the river outlet during the dry day and rainy days are recorded as 1640 NTU and 1290 mg/L and 2510 NTU and 2400 mg/L, respectively. The aesthetic appeal of the river is very repelling due to high turbidity and muddy appearance of the river. As such, proper integrated river basin management with necessary supports from the people and authorities are badly needed to rehabilitate Sg. Pusu which flows through the IIUM Gombak Campus.